Improving the buffering capacity of biodigesters charged with cassava wastewater : - Nguyen, Minh Triet (Can Tho University, 2017)
The obiectives of the thesis were: To study the differences in gas production and methane content of the gas in the dome compared with the plug-flow. To study the Sodium bicarbonate (NaB) and effluent (EF) output from bio-digester could help to buffer the pH in cassava waste water (CW) bio-digester plant for better anaerobic fermentation.